An Audit and Comparison of pH, Measured Concentration, and Particulate Matter in Mannitol and Hypertonic Saline Solutions - Carr, Christopher J.; Scoville, Jonathan; Ruble, James; Condie, Chad; Davis, Gary; Floyd, Candace L.; Kelly, Logan; Monson, Ken; Reichert, Ethan; Sarigul, Buse; Hawryluk, Gregory W. J. (Frontiers in Neurology, 2021)
Background: The preferred hyperosmolar therapy remains controversial. Differences in physical properties such as pH and osmolality may be important considerations in hyperosmolar agent selection. We aimed to characterize important physical properties of commercially available hyperosmolar solutions. Methods: We measured pH and concentration in 37 commonly-used hyperosmolar solutions, including 20 and 25% mannitol and 3, 5, 14.6, and 23.4% hypertonic saline. pH was determined digitally and with litmus paper. Concentration was determined by freezing point and vapor pressure osmometry. Salinity/specific gravity was measured with portable refractometry. Particulate matter was analyzed with filtration and light microscopy and with dynamic light scattering nephelometry. Results: pH of all solutions was below physiological range (measured range 4.13–6.80); there was no correlation between pH and solution concentration (R2 = 0.005, p = 0.60). Mannitol (mean 5.65, sd 0.94) was less acidic than hypertonic saline (5.16, 0.60). 14/59 (24%) pH measurements and 85/111 concentration measurements were outside manufacturer standards. All 36/36 mannitol concentration measurements were outside standards vs. 48/72 (67%) hypertonic saline (p < 0.0001). All solutions examined on light microscopy contained crystalline and/or non-crystalline particulate matter up to several hundred microns in diameter. From nephelometry, particulate matter was detected in 20/22 (91%) solutions. Conclusion: We present a novel characterization of mannitol and hypertonic saline. Further research should be undertaken, including research examining development of acidosis following hyperosmolar therapy, the relevance of our findings for dose-response, and the clinical relevance of particulate matter in solution.